Influence of High Temperatures and Heat Wave on Thermal Biology, Locomotor Performance, and Antioxidant System of High-Altitude Frog Nanorana pleskei Endemic to Qinghai-Tibet Plateau - He, Jie; Tang, Xiaolong; Pu, Peng; Zhang, Tao; Niu, Zhiyi; Meng, Fei; Xi, Lu; Ma, Ming; Wu, Juan; Ma, Miaojun; Chen, Qiang (Frontiers in Ecology and Evolution, 2021)
Investigating how highland amphibians respond to changes in ambient temperature may be of great significant for their fate prediction and effective conservation in the background of global warming. Here, using the field individuals as control group, we investigated the influence of high temperatures (20.5 °C and 25.5 °C) and heat wave (15.0 - 26.6 °C) on the thermal preference, critical thermal limits, locomotor performance, oxidative stress, and antioxidant enzyme activities in high-altitude frog Nanorana pleskei (3490 m) endemic to the Qinghai-Tibet Plateau (QTP). After two weeks of acclimation to high temperatures and heat wave, the thermal preference (Tpref), critical thermal maximum (CTmax), and range of tolerable temperature significantly increased, while the critical thermal minimum (CTmin) was significantly decreased. The total time of jump to exhausted significantly decreased and the burst swimming speed significantly increased in the frogs acclimated in high temperatures and heat wave compared with field group. In high temperatures groups, the level of H2O2 and lipid peroxide (Malondialdehyde, MDA), as well as the activities of glutathione peroxidase (GPX), glutathione reductase (GR), catalase (CAT), superoxide dismutase (SOD), and total antioxidant capacity (T-AOC) obviously increased in the liver or muscle. However, in heat wave group, the MDA content significantly decreased in the liver, and antioxidants activities were decreased in live and muscle except for the CAT activities obviously increased in the liver. These results indicated that N. pleskei could respond to the oxidative stress caused by high temperatures by enhancing the activity of antioxidant enzymes. The heat wave did not appear to cause oxidative damage in N. pleskei, which may be attributed to the fact that they have successfully adapted to the dramatic temperature fluctuations on the QTP.